2006
DOI: 10.1196/annals.1373.045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cryptosporidium among Dairy Cows in Thailand

Abstract: Cryptosporidium species are frequently associated with diarrhea among AIDS patients in Thailand, and dairy herds are a possible source of some of these infections. A cross-sectional study was performed to determine if Cryptosporidium is present among dairy cows in Thailand. Fecal samples were randomly collected from 363 Holstein-Friesian dairy cows from 108 of 860 farms in the Nong Pho region of central Thailand. The average prevalence of Cryptosporidium among dairy cows was 9.4%, according to an assay for Cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
0
6
5
Order By: Relevance
“…The current study has demonstrated a relatively low prevalence of Cryptosporidium infection (3.3%) in cattle on the six studied farms. This percentage is lower than those previously reported in studies conducted in Malaysia [13,14], Thailand [32][33][34], Vietnam [35], Sri Lanka [25] and China [36], which reported of prevalences ranging from 9.4% to 62.1%. In the present study, only C. bovis and C. ryanae were identified in the cattle, whilst C. parvum, the most common zoonotic species in cattle [2,37] was not detected in any of the tested samples.…”
Section: Resultscontrasting
confidence: 71%
“…The current study has demonstrated a relatively low prevalence of Cryptosporidium infection (3.3%) in cattle on the six studied farms. This percentage is lower than those previously reported in studies conducted in Malaysia [13,14], Thailand [32][33][34], Vietnam [35], Sri Lanka [25] and China [36], which reported of prevalences ranging from 9.4% to 62.1%. In the present study, only C. bovis and C. ryanae were identified in the cattle, whilst C. parvum, the most common zoonotic species in cattle [2,37] was not detected in any of the tested samples.…”
Section: Resultscontrasting
confidence: 71%
“…infections in cattle were 13% by AFS. This is higher than the prevalence (0.6%) of Cryptosporidium found among dairy cows in the Nong Pho region of central Thailand by AFS reported by Jittapalapong et al (2006) and lower than the prevalence of Cryptosporidium in Tanzania and Zambia (Swai et al 2007;Geurden et al 2006). However, Cryptosporidium infection correlated with host age, which is an important factor characterizing the distribution of Cryptosporidium infections and suggesting a degree of resistance conferred to individuals infected early in life (Arslan and Vicki 1999;Castro-Hermida et al 2002;Tanriverdi et al 2006;Kvac et al 2006;Lefay et al 2000;Geurden et al 2006;Azami 2007;Uga et al 2000;Nguyen et al 2007).…”
Section: Discussioncontrasting
confidence: 54%
“…Kaewthamasorn and Wongsamee (2006) screened 207 faecal samples of beef cattle in Nan Province, Northern Thailand but did not detect either parasite in their samples. While we did not detect either Cryptosporidium or Giardia in faecal samples of dairy cattle at our study site, other Thai studies have (Inpankaew et al, 2010;Jittapalapong et al, 2006Jittapalapong et al, , 2011Nuchjangreed et al, 2008). In Northern Thailand, the seroprevalence of Cryptosporidium parvum infection of 642 dairy cows were 3.3%, 5.1% and 3.0% in the provinces of Chiang Mai, Chiang Rai and Lampang, respectively (Inpankaew et al, 2009).…”
Section: Livestock Managementcontrasting
confidence: 42%